The Influence of Work Discipline on Employee Performance at the Makassar City Tourism Office - Hasriani Ramadani; Samsul Rizal; Sri Andayaningsih (CV. AFDIFAL MAJU BERKAH, 2024)
The purpose of this research is a type of quantitative research with the aim of finding out the effect of work discipline on employee performance at the Makassar City Tourism Office. This sample was taken from the Makassar City Tourism Office. The type of data used in this research is quantitative data obtained from distributed questionnaires and is related to the problem being studied. Data collection techniques were carried out using questionnaires, observation and documentation. In this research, the data sources used in data collection include primary data and secondary data. The research instrument used in this research used the Likert scale method. Based on the results of data research using statistical calculations through the Statistical for the Social Science (SPSS) version 20 application regarding the influence of work discipline on employee performance at the Makassar City Tourism Office which was discussed in the previous chapter, the author draws an important conclusion, namely that work discipline has a positive effect and significant in increasing employee performance at the Makassar City Tourism Office as evidenced by the work discipline regression coefficient (X) of 0.490 and the calculated t value of 3.051 > t table 0.679 with a significance value of 0.004 < 0.05.